Integrasi Kearifan Lokal Baduy Pada Pengembangan Bahan Ajar Modul IPA Dalam Menanamkan Nilai-Nilai Konservasi Lingkungan - Vania Ayushandra; Sri Wuryastuti (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The existence of globalization and modernization is the cause of various changes in a life, one of which is local wisdom. Local wisdom is now fading along with the rapid development of the times. The process of learning at the basic education level is to use the 2013 curriculum with integrative thematic learning, namely a learning model which consists of various themes in an integrated manner so that a meaningful experience can be obtained by students. The 2013 curriculum is based on cultural appreciation or local wisdom as stated in Permendikbud Nomor 79 Tahun 2014 concerning Local Content for the 2013 Curriculum. Teaching materials for thematic books are used nationally so that there is not enough local cultural wisdom for students. In the 2013 curriculum, science is one of the compulsory subjects. The principle of science learning is scientific inquiry with the surrounding environment, so it is very suitable if there is the involvement of Baduy local wisdom because in it Baduy is one of the Indonesian ethnic groups who are very close to nature. Therefore, researchers designed teaching materials in which there is local Baduy wisdom in an effort to instill environmental conservation values. In conducting this research, the researcher uses the R&D method, namely the ADDIE model with five stages. The teaching materials have been validated by material experts and media experts and given an assessment by the teacher which is stated in the appropriate category and without revision. The teaching materials developed were effective because all respondents gave positive responses and there was an increase in student learning outcomes before and after using the product.